At the crossroads : ICT policy making in East Africa - Elder, Laurent; Etta, Florence Ebam ([NetLibrary]., 2005)
This books presents the presents the findings of the mission. It is now being used to shape policy in Viet Nam and will continue to do so in the coming years. Interested readers will include government officials and policymakers in science and technology; academics, researchers, professors,and university students in development studies, policy studies, and Asian studies; public and private businesses involved, or interested in becoming involved, in the changing economy of Viet Nam; and donor organizations and NGOs active in Viet Nam and throughout Asia.